Competition policy, Developing Countries and the WTO - Bernard Hoekman; Peter Holmes (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper discusses developing country interests regarding the inclusion of competition law disciplines in the WTO. Although developing countries have a great interest in pursuing an active domestic competition policy, this can and should be done independently of the WTO. Given the mercantilist basis of multilateral trade negotiations, the WTO is less likely to be a powerful instrument to encourage adoption of welfare-enhancing competition rules than it is as a forum for the abolition of border measures. Priority should therefore be given to pursuit of the traditional market access focus of the WTO—further reduction in direct barriers to trade in goods and services.
Keywords: F13; L40; 330; Competition policy; Trade negotiations; World Trade Organisation; Economic development